2021
DOI: 10.1021/acsami.0c23058
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing the Diffusion of Fluorinated Polymers to Modify the Semiconductor/Dielectric Interface in Solution-Processed Conjugated Polymer Field-Effect Transistors

Abstract: It has been demonstrated that tailoring the properties of semiconductor/dielectric interfaces with fluorinated polymers yields better performance for organic field-effect transistors (OFETs). However, it remains a challenge to fabricate bottom-gate OFET devices on fluorinated dielectrics using solution-processed methods due to the poor wettability of fluorinated dielectrics. Here, we utilized the diffusion of fluorinated poly­(methyl methacrylate) (PMMA) to construct the fluorine-rich semiconductor/dielectric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 70 publications
0
22
1
Order By: Relevance
“…It is clearly observed that the introduction of -CF 3 into the PI system indeed decreases the trap depth in ESP map (Figure 1a-c) and increases the energy level of LUMO (Figure 1d-f), which indicates the reduction of the system polarizability due to the small dipole polarization ability of CF bonds. [23][24][25] In addition, the incorporation of -CF3 could effectively prevent the close accumulation of polymer chains to increase the fractional free volume of polymer dielectrics (Figure 1g-i) for higher light transmittance (Figure S1, Supporting Information). The PI-based phototransistor was fabricated using a bottom-gate top-contact geometry, as shown in Figure 2a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clearly observed that the introduction of -CF 3 into the PI system indeed decreases the trap depth in ESP map (Figure 1a-c) and increases the energy level of LUMO (Figure 1d-f), which indicates the reduction of the system polarizability due to the small dipole polarization ability of CF bonds. [23][24][25] In addition, the incorporation of -CF3 could effectively prevent the close accumulation of polymer chains to increase the fractional free volume of polymer dielectrics (Figure 1g-i) for higher light transmittance (Figure S1, Supporting Information). The PI-based phototransistor was fabricated using a bottom-gate top-contact geometry, as shown in Figure 2a.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] By using OFETs as a photosensitive unit, organic phototransistors (OPTs) have the dielectric layer and the maximum reduction of the generation of traps at the interface of semiconductor/dielectric layer, so as to impede the charge-trapping process and improve carrier mobility. [23][24][25] Although, some works have been done to prove that the devices with fluorinated PI could enhance the mobility, [26,27] the effect of the amount of fluorine functional groups on its mobility has not yet been studied, to say nothing of the modulation effect of fluorine functional groups on photogenerated charge carrier in phototransistors.…”
Section: Introductionmentioning
confidence: 99%
“…1-Ethyl-3-methylimidazolium tetrafluoroborate ([EIM]­BF 4 ) purchased from the Lanzhou Institute of Chemical Physics, Chinese Academy of Sciences, was used as a testing liquid to develop the wetting ridge for supported thin PS films. Silicon(100) (Si) wafers were used as a substrate after being washed with a piranha solution at 393 K for 30 min. By thorough rinsing with deionized water and nitrogen blow drying, the wafer surface was covered with a 2.2 nm oxide layer (Si/SiO x ) and exhibited a water contact angle θ of less than 10°.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…However, the doping process in the fabrication of OFETs remains challenging mainly because of their instability due to the uncontrollable dopant diffusion and low doping efficiencies. To solve these issues, several approaches have been proposed in the past few years; these can be classified into the following two categories: (1) Direct doping of specially designed inorganic or organic dopants into polymer semiconductors (e.g., self-compensated doping with covalently bonded dopants to the backbone or solution-based doping over a limited depth ) and (2) indirect doping by inducing polarization on the surfaces of dielectrics interfaced with polymer semiconductors (e.g., a self-assembled monolayer treatment with a specially designed functional group on the dielectric surface or the use of a dielectric layer containing fluorinated functional groups ).…”
Section: Introductionmentioning
confidence: 99%